Actual and Potential Pedagogical Use of Tablets in Schools - Rikala, Jenni; Vesisenaho, Mikko; Mylläri, Jarkko (Human Technology, 2013)
This study reviews the potential of tablet technology for teaching and learning. In autumn 2012, we conducted a focused survey comprising quantitative and qualitative questions with Finnish teachers (N = 171, from 54 schools). We focused on perceived pedagogical opportunities and the actualized pedagogical potential of tablets at schools. The survey results indicate that the actual usefulness of tablets in schools was significantly less than what teachers perceived as the pedagogical potential. However, the results demonstrate the positive impact these devices are having on teaching and learning, as well as prompting changes in pedagogical perspectives. Teachers stated that tablets can diversify and enhance teaching and learning in many ways, particularly in supporting learners' motivation and independent learning, and promoting engaging teaching methods. Nevertheless, teachers voiced concern that the student-to-device ratio at the moment is too low, thus serving as a barrier to widespread use of tablets.